SISTEM KENDALI SUHU PADA PENGERINGAN ECENG GONDOK BERBASIS HMI - Rahmansyah, Hanif Dwi (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Water hyacinth (Eichornia crassipes) is a water weed that has a harmful impact on the aquatic ecosystem. It has a high nutrient content, including 4.08% crude fiber, 3.55% crude protein, 8.22% carbohydrates, and 3.93% ash. Because of these contents, water hyacinth is suitable as fish food. One potential technology that can be develop from existing research to address this issue is a temperature control system for water hyacinth. This system would utilize an Outseal Nano processor with a Human Machine Interface (HMI) and a PID controller based on the Ziegler-Nichols method. Drying would occur at 60°C and 75°C for 60 minutes. Research findings with parameters Kp = 6.25; Ki = 58.5; and Kd = 0.3 indicate that the system response has a rise time of 0.0988s, a settling time of 0.4280s, and an overshoot of 12.5224%. At a drying temperature of 60°C for 60 minutes, the water hyacinth reaches a dryness of 63.3%, while at a temperature of 75°C for 60 minutes, it reaches a dryness of 70%. This research has proven that using PID control produces a more effective system.